Teologi Rasional Ijtihad Dan Dogmatis Taqlidi Penalaran Filsafat Kalam - Teuku Safir Iskandar Wijaya (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2017)
The ideas of rational theology and dogmatic theology are closely related to the concept of taqlid and ijtihad in the development of Islamic theological thought. Even, both theologies have caused serious debates among Islamic thinkers and mutakallim from time to time. In this relation, two different ideas arise; some say the door of ijtihad is closed for everything; in addition, there is also a view that the door of ijtihad only closed in relation to theological belief, and still open for muamalah problem, and law related to humanity problem. The question that arises in this connection is